Genetics of aging and longevity - A. A. Moskalev; E. N. Proshkina; A. A. Belyi; I. A. Solovyev (Вавиловский журнал генетики и селекции)
Lifespan is a complex quantitative characteristic that makes a significant contribution to the Darwinian adaptiveness. The disclosure of the genetic structure of longevity is a fundamental problem of the evolution of ontogeny, evolutionary genetics and molecular gerontology. Under optimal conditions, the lifespan is determined by the aging rate. The aging process is made up of interrelated processes that take place at the organismal, tissue, cellular, molecular and genetic levels. These include deregulation processes of homeostasis maintenance, metabolic reactions and sending intra- and intercellular signals, accumulation of senescent cells, damaged organelles and macromolecules, epigenetic changes and genetic instability. The objective of this review is to summarize the available information about underlying genetic determinants of longevity and aging. Genes and signaling pathways that regulate stress response, metabolism, growth of cells and organism, maintaining of genome and proteome integrity, qualitative and quantitative mitochondria composition, inflammatory response, apoptosis and selection of viable cells, as well as circadian rhythms were considered. The redistribution of energy resources from one pathway to the other can induce or inhibit the ”longevity program”, providing increased vitality and aging slowdown. Based on the analysis of geroprotective potential of examined genes’ regulation, main targets have been identified to slowdown aging and achieve healthy longevity. These trends include heterochromatin recovery, retrotransposition suppression, aneuploidy elimination; restoring the acidity of lysosomes; telomere elongation; suppression of chronic inflammation; elimination of protein cross-links; elimination of senescent cells; recovery of NAD+ levels; inhibition of mTOR, S6K, TGF-β, AT1; controlled activation of the ”longevity program” genes FOXO, AMPK, PGC1α, NRF2.